Protocatechuic acid as an inhibitor of lipid oxidation in meat - Deuchande, Teresa; Fundo, Joana F.; Pintado, Manuela E.; Amaro, Ana L. (Meat science, 2024)
Lipid oxidation is the principal driver of meat and meat product deterioration during shelf life, causing the loss of fresh meat color, flavor, and aroma. Currently, synthetic antioxidants are used to prevent oxidation, but increasing consumer demand for natural ones leaves the industry with few alternatives. In this study, protocatechuic acid (PCA), known to have high antioxidant activity, was evaluated as a potential inhibitor of meat lipid oxidation. For this purpose, the antioxidant capacity and lipoxygenase (LOX) inhibitory activity of PCA were evaluated in vitro, and a set of four experiments was conducted, treating minced meat with water (control), lactic acid (LA), rosmarinic acid (RA) and PCA, at different concentrations (1–12 mg mL−1), depending on the experiment. The potential antioxidant effect of PCA when applied to meat cubes was also evaluated, as well as the potential of carboxymethyl cellulose (CMC) as a delivery system for PCA. The in vitro results showed that PCA is a potent antioxidant and an effective LOX inhibitor at 1 mg mL−1. PCA effect on meat lipid oxidation prevention was dose-dependent, and at 2 mg mL−1, it inhibited color change by 50% and lipid peroxidation by up to 70% when compared to water-treated samples, performing better than RA at 0.25 mg mL−1. These results suggest that PCA is a promising molecule to the meat industry as a natural preservative for meat and meat products directly or in a formulation.